Sound wave propagation problems new perturbation methodology - Skrzypczyk, Jerzy; Winkler-Skalna, A. (Archives of Acoustics, 2006)
The aim of the paper is to present applications of the new algebraic system theory in acousticproblems. Elements of new types of perturbed ordinary and partial differential equationsare discussed. The formulation is applied to the analysis of perturbed wave problems withperturbations in parameters as well as in initial and boundary conditions. Classical perturbationacoustic problems described by differential equations can be solved in the modifiedalgebraic system as easy as usual. Any additional analytical transformations are not required.A novel 2D ray-tracing model of detailed representation of the indoor/outdoor environmentis presented. Perturbation ray tracing method is a technique based on geometrical optics withperturbation in parameters which can be an easily applied approximate method for estimatingperturbation problems in acoustics. The developed algorithms use the new perturbationmethodology where the perturbed images are used to produce 2D-field of illumination zones.It can be easy considered how perturbations (small) of nominal parameter values can changesolutions of the considered problems.